Analysis of Tourism Village Management in Wewengkon Kasepuhan Customary Citorek, Lebak Regency, Banten Province-Indonesia - Mariati, Sri; Prabowo, Yogan Daru; Rahmanita, Myrza; Habibie, Fachrul Husain; Mustika, Amalia (Institut Pariwisata Trisakti, 2023)
Wewengkon Adat Kasepuhan Citorek is a traditional rural area which is one of the priorities for tourism development in Lebak Regency. As a traditional village that has unique cultural potential, this area also has a variety of natural potential because of its position as an enclave area of the Gunung Halimun Salak National Park (TNGHS), so it is not surprising that this area is directed to be developed as a tourist village thanks to the potential it has. This research aims to identify and analyze tourist village management based on tourist village components in Wewengkon Adat Kasepuhan Citorek. The research method used is a descriptive analysis method by comparing conditions in the field with the theory of tourist village components. The results of this research are that the management of tourist villages in Wewengkon Adat Kasepuhan Citorek is still natural and there is no special tourism village management so that each village runs independently. Therefore, it is necessary to have a tourist village management institution with a cluster model so that each village complements and integrates each ODTW as a form of shared enthusiasm in managing tourist villages in Wewengkon Adat Kasepuhan Citorek. Keywords: Tourism Village, Tourism Village Components, Institutions, Management